Biosorption of zinc (II) Ions from aqueous solution by mango seeds - Ng, Pey Xuan (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
Contamination of water by heavy metals threatens the well-being of humans and the natural environment. The need for a cost-effective and efficient method for the metal ions removal has led researchers to develop interest in biomass that can be used as adsorbent to accumulate the toxic metals. This research was conducted to determine the potential of the waste biomass of Mangifera indica seed as low cost biosorbent in binding with the zinc (II) ions present in the aqueous solution. Research was carried out by testing the sorption capabilities of the pH, the biosorbent dosage, the contact time, and the concentration of zinc metal variation. The mango seeds biosorbent was found effective in zinc ion removal where the maximum sorption capacity could reach 57.03 mg/g and the maximum percentage removal was 89.25%. The optimum condition for the biosorption to occur were at pH 6 with sorption capacity of 55.08 mg/g, 50 mg/L of initial zinc ion concentration with sorption capacity of 55.49 mg/g and 0.1 g biosorbent dosage that obtained 54.53 mg/g of sorption. The sorption process of the zinc ions onto the mango seeds biosorbent obeyed Pseudo-Second with linearity of 0.9692 while the adsorption followed the Langmuir isotherm with linearity 0.9986 implied that chemisorption took place with monolayer sorption process. Fourier Transformed Infrared Spectroscopy (FTIR) technique was used to characterize the mango seed biosorbent. FTIR analysis shown that phenolic (--O--H) group, primary amines (--N--H) group and aliphatic amines (--C N) group interact with the zinc metal ions. The experiments result revealed that biosorbent derived from mango seeds represent an attractive candidate to remove zinc metal ions